THE INFLUENCE OF LEARNING MOTIVATION ON LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION SUBJECTS IN ISLAMIC JUNIOR HIGH SCHOOL STUDENTS JATISRONO WONOGIRI MUSLIM ACADEMIC YEAR 2022/2023 - Irfan Imaddudin Alfaruqi; Nur Hidayah; Sugiyat Sugiyat (Jurnal Scientia, 2023)
This research uses a quantitative method with a correlational quantitative type where the research focuses on the influence of the independent variable on the dependent variable. The research will be carried out at the Jatisrono Muslim Middle School, Wonogiri, by taking samples from three levels, namely grades 7, 8 and 9. Data collection was carried out using questionnaires and documentation methods. Data analysis uses simple regression analysis techniques. The results of the research show that student learning motivation is based on an average of 59.93, indicating that the average student at the Jatisrono Muslim Middle School, Wonogiri, Academic Year 2022/2023 has moderate learning motivation. Meanwhile, the average student learning outcomes for PAI subjects is 85.93, which shows that the average student at the Jatisrono Muslim Cluster Islamic Middle School, Wonogiri, for the 2022/2023 academic year has moderate learning motivation. Besides that, the results of the linear regression test in the Anova table show that the calculated F is 6.639, which means that the calculated F is greater than the F table (3.95), so Ha is accepted and H0 is rejected. So it can be concluded that there is an influence of learning motivation on PAI learning outcomes for Islamic Middle School students at the Jatisrono Muslim Community, Wonogiri, academic year 2022/2023.